Impact of raw water turbidity fluctuations on drinking water quality in a distribution system. Issue 4 (1st July 2003) - Gauthier, Vincent; Barbeau, Benoit; Tremblay, Geneviève; Millette, Robert; Bernier, Anne-Marie
Abstract : Turbidity is a widely used parameter around the world for describing drinking water quality. Sometimes, turbidity at water treatment plant outlets may reach high values during short periods of time, and this is acceptable according to some current drinking water regulations. In this study, the quantity and nature (chemical and microbiological) of suspended matter, which may travel throughout a distribution system (DS) during turbid events affecting both raw water and water treatment were evaluated. Treated water included filtration with no coagulant addition. During turbid events, the concentration of suspended particles increased in treated water, and a similar increase (quantity and nature) was observed throughout the DS. Bacterial indicators of contamination (total and fecal coliforms, enteroccocci, spores of Clostridium perfringens ) were not found in either treated water nor in the DS during turbid events. Nevertheless, a higher bacterial aerobic spore concentration was associated with turbid events for raw, treated, and distributed water, therefore suggesting the potential passage of pathogens, if present in raw waters. Cultivable bacteria concentrations remained low in treated and distributed water regardless of the turbidity. These results emphasize the need to carefully monitor raw and treated water quality for utilities using "high quality" water resources with limited treatment barriers, especially when such water resources are affected by even slight turbidity variations. Key words: aerobic spore-forming bacteria, distribution system, drinking water, filtration, turbidity, suspended particles, water quality.